2014
DOI: 10.1007/s10971-014-3398-1
|View full text |Cite
|
Sign up to set email alerts
|

The sol–gel approach as a method of synthesis of xMgO·ySiO2 powder with defined physicochemical properties including crystalline structure

Abstract: The physicochemical properties of synthetic powders depend strongly on the method of their preparation. The present work concerns the use of the sol-gel method to prepare xMgOÁySiO 2 powders with defined physicochemical and structural properties. An important objective was to determine how the basic process parameters (including the type and concentration of the reactants) influence the physicochemical properties of the resulting material. To obtain a synthetic powders, organic precursors of magnesium (magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…In a recent publication, Ciesielczyk et al . confirmed the strong influence of sol–gel process parameters on physicochemical properties of the resulting x MgO⋅ y SiO 2 materials (one of these materials is similar to an organotalc).…”
Section: Talc‐like Structuresmentioning
confidence: 91%
“…In a recent publication, Ciesielczyk et al . confirmed the strong influence of sol–gel process parameters on physicochemical properties of the resulting x MgO⋅ y SiO 2 materials (one of these materials is similar to an organotalc).…”
Section: Talc‐like Structuresmentioning
confidence: 91%
“…The sol-gel method is a very flexible route for the synthesis of advanced materials in a wide variety of forms, such as spherical or ultrafine shaped powders, fibers, thin film coatings, dense or porous materials including highpurity inorganic oxides and hybrid (inorganic-organic) materials [23][24][25][26][27]. The sol-gel process is a useful synthetic method for the preparation of amorphous, as well as structurally ordered, materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very important fact with regard to the adsorption of positively charged metal ions, as is the quantity of active hydroxyls present on the adsorbent surface as confirmed by the FTIR spectrum of the analyzed sample. The FTIR spectrum also shows signals characteristic for sol-gel-derived MgO-SiO 2 oxide adsorbent: 3650-3350 cm -1 -stretching vibrations of hydroxyls; 1050 cm -1 and 890 cm -1 -stretching vibrations of Si-O bonds; 645 cm -1 -deformation vibrations of Si-O-Mg bonds; 630 cm -1 -deformation vibrations of OMg-O bonds; 540 cm -1 -stretching vibrations of O-Si-O (Chabrol et al 2010;Ciesielczyk et al 2014;Lan et al 2012;Vishwas et al 2011). According to the literature (Karthik and Meenakshi 2015a, b), low pH values are unfavorable for metal ion adsorption, since in that range they are present in solution in free form as M n?…”
Section: Sorption Processmentioning
confidence: 95%
“…Due to the methodology of synthesis the amount of moisture was limited and was no more than 10 %. The results also showed that the resulting inorganic oxide adsorbent has a completely amorphous structure, which can be transformed into crystalline by the selection of an appropriate heat treatment technique (Ciesielczyk et al 2014). On the one hand it is possible to obtain crystalline powder adsorbent, Crystalline structure SEM image in the scale of 1 lm while on the other the moisture content can be completely reduced; this determines the surface activity, translating into a quantity of reactive silanol and magnesil groups (:Si-OH and -Mg-OH).…”
Section: Adsorbent Characterizationmentioning
confidence: 98%
See 1 more Smart Citation